PEMBERIAN REMISI TERHADAP NARAPIDANA KASUS KORUPSI SEBAGAI WUJUD PEMBINAAN DALAM PEMENUHAN HAK ASASI MANUSIA (Studi Kasus di Lembaga Pemasyarakatan Klas IIA Yogyakarta - , SOLEH JOKO SUTOPO, Prof. Dr. Edward Omar Sharif Hiariej, SH.,M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is aimed to understand about remission offering upon corruption case prison inmate as the implementation of recovery and fulfilling their human rights. This research is normative research, namely proses to find a juridical rule, juridical principes, juridical doctrines to answer law problem confronted. This normative law research is purposed to give law argumentation as a basic determination if a case are right or wrong, also the best method to treat the case as appropriate with the law. Data is obtained through documentation study, and analysed then via qualitative descriptive namely data are served descriptively and analysed then qualitatively to be concluded as the answer of the case in the research. The result of the research : (1) amount of prison inmate of corruption case until March 2012 are 26 (twenty six) people. Whereas the variation of imprisonment of the prison inmate of corruption case are varied between 1 (one) year up to 4 (four) years. Based on the data from Class II A Prison of Yogyakarta, it is obtained information that one prison inmate of corruption case who accept remission of its punishment during three month of year 2011 with the description for general remission for 2 (two) months and specific remission for 1 (one) month. For that reason, the remission for prison inmate of corruption case that implemented by Class II A Prison of Yogyakarta is accepted by one person only that is during year 2011. Another prison inmate donât accept the specific remission yet for corruption case